NORMAL SERUM VITAMIN B12 LEVELS IN SYMPTOMATIC PATIENTS: DIAGNOSTIC VALUE OF METHYLMALONIC ACID AND HOMOCYSTEINE IN FUNCTIONAL DEFICIENCY - Nieścioruk, Michalina Weronika; Kozdroń, Dominika Julia; Szczepańska, Paulina; Kowalski, Jacek; Dutkiewicz, Dominika; Yarbou, Alia Echtay; Mallah, Rami; Mikołajuk, Adrian (International Journal of Innovative Technologies in Social Science, 2026)
Background: Vitamin B12 deficiency is a clinically important condition associated with hematological, neurological, and neuropsychiatric manifestations. However, diagnosis may be difficult in symptomatic patients with normal total serum vitamin B12 concentrations, as normal circulating levels do not necessarily reflect adequate intracellular metabolic function. This has led to growing interest in the concept of functional vitamin B12 deficiency. The aim of this review was to evaluate the diagnostic value of methylmalonic acid (MMA) and homocysteine in symptomatic patients with normal or borderline serum vitamin B12 levels.Methods: A narrative review was conducted using the PubMed database. English-language peer-reviewed articles published over the last decade were screened for relevance to vitamin B12 metabolism, laboratory assessment, functional deficiency, and the diagnostic utility of MMA, homocysteine, and holotranscobalamin. Eighteen publications were included in the qualitative synthesis.Results: Total serum vitamin B12 has limited sensitivity for early or functional deficiency. MMA and homocysteine reflect metabolic consequences of impaired vitamin B12–dependent pathways and may improve diagnostic sensitivity in patients with normal or borderline serum levels. MMA is more specific for vitamin B12–related metabolic impairment but is influenced by renal function and age. Homocysteine is less specific and is affected by folate and vitamin B6 status, renal function, and age. Holotranscobalamin reflects the circulating biologically active fraction of vitamin B12 and may allow earlier detection of reduced availability. Biomarker interpretation is limited by physiological and inter-individual variability, as well as the lack of standardised cut-off values. Conclusions: In symptomatic patients with inconclusive serum vitamin B12 results, MMA and homocysteine provide clinically relevant complementary information. A combined diagnostic approach integrating serum vitamin B12, functional biomarkers, and clinical assessment offers greater diagnostic accuracy than reliance on total serum vitamin B12 alone.